Administrative and Criminal Law Aspects of Public Procurement: Their Role in Promoting Accountable Procurement Practices: Aspek Hukum Administrasi dan Hukum Pidana dalam Pengadaan Barang dan Jasa: Peranannya dalam Mewujudkan Pengadaan Barang dan Jasa yang Akuntabel - Eduard Awang Maha Putra; Hamdani, Fathul; Ana Fauzia; Gea Ossita S.; Baiq Amilia Kusumawarni (Universitas Islam Indonesia, 2024)
Procurement of goods and services must be based on the principle of accountability to achieve procurement of goods and services that can advance public welfare and provide protection and fulfillment of human rights. It can be said that corrupt practices by government agencies and institutions at the central, regional, and other government institutions are easily carried out in the procurement of goods and services. The purpose of this study is to examine the aspects of administrative law and criminal law in the procurement of goods and services, as well as their role in realizing accountable procurement of goods and services. The method of writing this article is normative legal research with a statutory and conceptual approach. The results of the study show that in the aspect of administrative law, one of the inherent functions is the regulatory function. This regulatory function is related to the legal relationship between providers and users in the preparation process up to the process of issuing a letter of determination of providers of goods and services. This administrative law can be an instrument for building a paradigm that leads to the implementation of accountable procurement of goods and services, because, through its regulatory function, additional indicators can be created for users of goods and services in decision-making, such as the requirement for anti-bribery certification and assessment based on performance track records that have not been implemented in Indonesia. If a criminal offense is committed by the user or provider of goods or services during the procurement process, then the criminal law aspect of procurement will be applied. Therefore, it is important to have a kind of paradigm development that leads to accountable procurement of goods and services to avoid potential criminal violations.Keywords: State Administrative Law, Criminal Law, Procurement of Goods and Services AbstrakKegiatan pengadaan barang dan jasa harus dilandasi dengan prinsip akuntabilitas agar tercapai pengadaan barang dan jasa yang dapat memajukan kesejahteraan umum serta memberikan perlindungan dan pemenuhan hak asasi manusia. Karena dapat dikatakan bahwa praktik-praktik korupsi oleh badan-badan dan lembaga-lembaga pemerintah di tingkat pusat, regional, dan lembaga-lembaga pemerintah lainnya dengan mudah dilakukan dalam pengadaan barang dan jasa. Tujuan penelitian ini adalah mengkaji aspek hukum administrasi dan hukum pidana dalam pengadaan barang dan jasa, serta pernanannya dalam mewujudkan pengadaan barang dan jasa yang akuntabel. Metode penulisan artikel ini adalah penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian menunjukkan bahwa dalam aspek hukum administrasi, salah satu fungsi yang melekat adalah fungsi mengatur. Fungsi mengatur ini berkaitan dengan hubungan hukum antara penyedia dan pengguna pada proses persiapan sampai dengan proses penerbitan surat penetapan penyedia barang dan jasa. Hukum administrasi ini dapat menjadi instrumen untuk membangun paradigma yang mengarah pada pelaksanaan pengadaan barang dan jasa yang akuntabel, sebab melalui fungsi mengaturnya, dapat dibuat indikator-indikator tambahan bagi pengguna barang dan jasa dalam pengambilan keputusan, seperti keharusan adanya sertifikasi anti suap dan penilaian berdasarkan track record kinerja yang selama ini belum diterapkan di Indonesia. Jika pelanggaran pidana dilakukan oleh pengguna atau penyedia barang atau jasa selama proses pengadaan, maka aspek hukum pidana dari pengadaan akan diterapkan. Oleh karena itu penting ada semacam pembangunan paradigma yang mengarah pada pengadaan barang dan jasa yang akuntabel sehingga terhindar dari potensi pelanggaran pidana.Kata Kunci: Hukum Administrasi Negara, Hukum Pidana, Pengadaan Barang dan Jasa